Marine Debris Governance: Global Research Trends - Muh. Ersyad Indra Praja; Ahmad Suryadi; Suprianto Suprianto; A. Alifka Ramadhana; Nurfadillah Nurfadillah; Tri Nurfadilla (Jurnal Riset Diwa Bahari (JRDB), 2024)
Marine debris has become one of the most pressing global environmental challenges, threatening marine ecosystems, biodiversity, coastal livelihoods, and human well-being. In response, governance approaches have evolved to address the complexity of marine debris through integrated policies, multi-stakeholder collaboration, and sustainable resource management. Despite the rapid growth of research in this field, a comprehensive synthesis of its intellectual development and emerging trends remains limited. This study aims to examine global research trends on marine debris governance through a Systematic Literature Review with Bibliometric Analysis. Relevant publications were retrieved exclusively from the Scopus database using predefined search criteria and systematically screened following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. Descriptive bibliometric analysis was employed to identify publication trends, leading journals, countries, institutions, and influential authors, while VOSviewer was used to visualize keyword co-occurrence, collaboration networks, and thematic evolution. The findings indicate a substantial increase in scholarly attention to marine debris governance over the past decade, with dominant research themes including marine plastic pollution, waste management, circular economy, environmental policy, stakeholder collaboration, and coastal governance. Emerging topics such as blue economy, ecosystem-based management, citizen science, and environmental justice demonstrate the evolving interdisciplinary nature of the field. Nevertheless, significant research gaps remain regarding policy integration, governance effectiveness, transboundary cooperation, and the implementation of sustainable marine waste management strategies. This review provides a comprehensive overview of the knowledge structure and development of marine debris governance research while identifying future research priorities to support evidence-based policymaking and sustainable ocean governance.